FOSS BASED AIR TRAFFIC CONTROL SIMULATOR - Dabare, Poshitha; Dias, GKA; Nisansala, Aruni; Weerasinghe, Maheshya; Sandaruwan, Damitha; Kodikara, Nihal; Keppitiyagama, Chamath; Dhammika, Nuwan; Lakshika, Chamal; Buddhika, Ishan (International Journal of Research -GRANTHAALAYAH, 2016)
This paper presents an analysis of the significance of Air Traffic Control (ATC) simulators in training, and focuses on the development of low cost, high awareness ATC simulator on a 3D virtual environment, using Free and Open Source Aircraft simulator named Flightgear. Here it has proposed a scenario based ATC officer control method covering the all three phases; tower control, approach and enroute control.